Analisis Penerapan Proses Akuntansi Manajemen Pada UMKM Tao Toba - Tirza Venisia Sinambela; Hany Putri Br. Sitanggang; Ratih Kusumastuti (Institut Nalanda, 2023)
The aim of this research is to conduct an in-depth analysis of the application of management accounting principles in Tao Toba micro, small and medium enterprises. The object of this research is Tao Toba micro, small and medium enterprises located on Jl.Ir.H.Juanda, Mayang, Jambi City. This research method is a descriptive approach with qualitative methods and by conducting direct interviews with the owner. The results of this research indicate that significant improvements need to be made in the financial management aspects of micro, small and medium enterprises. Micro, small and medium business owners need to carry out training on the use of modern accounting systems and management accounting practices.